Modern Arabic literature - Starkey, Paul, 1947- (Edinburgh : Edinburgh University Press, 2006)
Provides an introduction to modern Arabic literature of the nineteenth and twentieth centuries. Designed as an introductory textbook for English-speaking undergraduates, this title attempts to situate the development of modern Arabic literature in the context of the medieval Arabic literary tradition.
The background -- The revival -- Neo-classical poetry -- Romanticism in Arabic poetry -- Poetry : the modernists -- Prose literature : early developments -- Prose literature : the period of maturity -- The sixties generation and beyond -- Drama : early experiments -- Drama : the period of maturity.
Includes bibliographical references (pages 201-211) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Arabic literature -- 1801- -- History and criticism; Littérature arabe -- 19e siècle -- Histoire et critique; LITERARY CRITICISM -- African; LITERARY COLLECTIONS / General; Arabic literature; Literatur; Arabisch; Arabisch; Since 1801; Geschichte 1800-2000; Electronic book; Criticism, interpretation, etc